2016
DOI: 10.1182/blood-2016-02-701094
|View full text |Cite
|
Sign up to set email alerts
|

Disseminated intravascular coagulation at diagnosis is a strong predictor for thrombosis in acute myeloid leukemia

Abstract: Key Points• A high D-dimer level strongly predicts symptomatic venous and arterial thrombosis in newly diagnosed AML.• Thrombosis occurs in up to 10% of patients with newly diagnosed AML.Venous thromboembolism is a common complication in patients with cancer, but only limited data are available in acute myeloid leukemia (AML). In a prospective study in a cohort of 272 adult patients (aged 18-65) and an independent validation cohort of 132 elderly adults (aged >60) with newly diagnosed AML, we assessed markers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
76
3
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(88 citation statements)
references
References 36 publications
5
76
3
4
Order By: Relevance
“…Regrettably, antithrombin levels that have been shown to increase the risk of thrombosis were not routinely collected at the time of patient enrolment in this study . A recent study on acute myeloid leukemia patients suggests that a situation parallel with disseminated intravascular coagulopathy (i.e., low platelet count, low TT%, and high D‐dimer) could increase the risk of venous thrombosis . Unfortunately, although our CVT patients showed a decreased level of platelets and elevated level of D‐dimer, no TT% was measured at the time of ALL diagnosis.…”
Section: Discussionmentioning
confidence: 93%
“…Regrettably, antithrombin levels that have been shown to increase the risk of thrombosis were not routinely collected at the time of patient enrolment in this study . A recent study on acute myeloid leukemia patients suggests that a situation parallel with disseminated intravascular coagulopathy (i.e., low platelet count, low TT%, and high D‐dimer) could increase the risk of venous thrombosis . Unfortunately, although our CVT patients showed a decreased level of platelets and elevated level of D‐dimer, no TT% was measured at the time of ALL diagnosis.…”
Section: Discussionmentioning
confidence: 93%
“…In addition to previously known prognostic factors, independent risk factors for thrombosis also include increasing age and cytogenetic risk [32,33]. Recently, disseminated intravascular coagulation was found to be significantly predictive of venous and arterial thrombosis, with thrombosis incidence being approximately 10% among patients who were treated with multiple rounds of chemotherapy [34]. Recent data suggest that malignant leukocytes mediate both disseminated intravascular coagulation and primary hyperfibrinolysis in acute promyelocytic leukemia [35].…”
Section: Discussionmentioning
confidence: 99%
“…Concerning haematological malignancies, some predictive models have been developed to identify patients at risk of VTE development, such as the ThroLy score, which was validated by Antic et al [24] in lymphoma patients with variables including previous venous and/or arterial events, mediastinal involvement, BMI > 30, reduced mobility, extranodal localization, development of neutropenia, and haemoglobin < 100 g/L. In newly diagnosed acute myeloid leukaemia (AML) patients, Libourel et al [25] showed that disseminated intravascular coagulation (DIC) markers at diagnosis are strong predictors for both arterial and venous thrombosis.…”
Section: Introductionmentioning
confidence: 99%